RAD51 modulates in nasopharyngeal carcinoma cells by regulating Caspase-8-mediated pyroptosis - Fuchuan Xie; Jian Song; Yunming Tian; Xinyu Zhang; Tanhuan Chen; Meng Xu (Discover Oncology)
Abstract Objective Radiotherapy is a first-line treatment for nasopharyngeal carcinoma (NPC), but resistance to radiation remains a major clinical challenge. This study aimed to investigate the role of RAD51, a key homologous recombination repair protein, in radiotherapy resistance of NPC and to elucidate its underlying molecular mechanisms. Methods RAD51 expression levels were examined in tumor and adjacent normal tissues from 20 NPC patients and in the radioresistant NPC cell line CNE2. Functional assays were conducted using recombinant RAD51 protein, the RAD51 inhibitor B02, and the Caspase-8 inhibitor Z-IETD-FMK. Changes in cell viability, lactate dehydrogenase (LDH) release, and expression of pyroptosis-related proteins were analyzed to assess the effects of RAD51 modulation. Results RAD51 expression was significantly elevated in NPC tumor tissues and CNE2 cells compared to normal controls (P < 0.05). Recombinant RAD51 protein enhanced CNE2 cell viability and inhibited Caspase-8-mediated pyroptosis pathways (P < 0.05). Inhibition of RAD51 by B02 reduced its expression and cell viability (P < 0.05), while the addition of Z-IETD-FMK further suppressed pyroptosis and promoted survival in RAD51-overexpressing cells (P < 0.05). Conclusion This study is the first to demonstrate that RAD51 promotes radiotherapy resistance in NPC cells by suppressing Caspase-8-dependent pyroptosis. These findings suggest that targeting RAD51 may represent a novel strategy to overcome radioresistance and improve therapeutic outcomes in NPC.